Mesopic and Photopic Rod and Cone Photoreceptor-Driven Visual Processes in Mice With Long-Wavelength-Shifted Cone Pigments - Tsai, Tina I.; Joachimsthaler, Anneka; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)
The clearer divergence in spectral sensitivity between native rod and human L-cone (L*-cone) opsins in the transgenic Opn1lwLIAIS mouse (LIAIS) allows normal visual processes mediated by these photoreceptor subtypes to be isolated effectively using the silent substitution technique. The objective of this study was to further characterize the influence of mean luminance and temporal frequency on the functional properties of signals originating in each photoreceptor separately and independently of adaptation state in LIAIS mice.Electroretinographic (ERG) recordings to sine-wave rod and L*-cone modulation at different mean luminances (0.1-130.0 cd/m2) and temporal frequencies (6-26 Hz) were examined in anesthetized LIAIS (N = 17) and C57Bl/6 mice (N = 8).We report maximum rod-driven response with 8-Hz modulation at 0.1 to 0.5 cd/m2, which was almost four times larger than maximum cone-driven response at 8 Hz, 21.5 to 130 cd/m2. Over these optimal luminances, both rod- and cone-driven response amplitudes exhibited low-pass functions with similar frequency resolution limits, albeit their distinct luminance sensitivities. There were, however, two distinguishing features: (1) the frequency-dependent amplitude decrease of rod-driven responses was more profound, and (2) linear relationships describing rod-driven response phases as a function of stimulus frequency were steeper.Employing the silent substitution method with stimuli of appropriate luminance on the LIAIS mouse (as on human observers) increases the specificity, robustness, and scope to which photoreceptor-driven responses can be reliably assayed compared to the standard photoreceptor isolation methods.
EVALuna2:21338
Keywords: Cone; Photoreceptor isolation; Rod; Electrophysiology; Mouse model